From Wrong Living to Right Living: Understanding the Desistance Process of Filipino Parolees - Abog, Karyl Christine A. (LIRIP Journal of Interdisciplinary Studies; Vol 4 (2022): LIRIP Journal of Interdisciplinary Studies, 2023)
Narratives of (13) Filipino parolees who were regarded as having successful reintegration experiences were analyzed to understand their desistance process: forming a commitment to change, persisting with discontinuance amidst setbacks, and maintaining the decision to stop. Key components that impeded and facilitated parolees’ reintegration into life outside of prison were examined. Family destabilization, psychosocial distress, diminished employment opportunities, housing and homelessness, and stigma were the challenges that they had to navigate. Factors that helped parolees facilitate the desistance process included supportive others, employment, schooling, agency, correctional/parole officers, spirituality, and parole itself. Narratives reflect that desistance, which commences during incarceration, is a result of the combination of individual factors and situational contexts that buffer the negative implications of having a history of offending.